Análise estrutural, avaliação do potencial antibiofilme e atividade antibacteriana de HGA-2, lectina de Holothuria grisea, em combinação com antibióticos - Tabosa, Pedro Arthur Sousa (2024)
Echinoderms (from the Greek echinos, “thorny”; derma, “skin”) are a group of animals that belong to the phylum Echinodermata. This phylum comprises approximately 7,000 living species and about 13,000 fossil species. A lot of natural substances with bioactive properties have been isolated from echinoderms, including: sulfated polysaccharides, glycoproteins, peptides, lectins and others. Invertebrates do not have an adaptive immune system. In echinoderms, it is accepted that lectins can be an important role in the immune system, functioning as key molecules in the body's immune response. HGA-2 was purified by affinity chromatography on guar gum and the protein was eluted with EDTA. HGA-2 showed greater affinity for carbohydrates and glycoproteins that present galactose residues in their structural conformations. In addition to saccharides, the hemagglutinating activity of HGA-2 was also inhibited by glycoproteins such as porcine stomach mucin type II, asialofetuin and thyroglobulin. With the exception of CEL-IV, analysis of the known amino acids of HGA-2 showed greater similarity with a putative lectin from Holothuria leucospilota. HGA-2 also showed a greater phylogenetic relationship with echinoderm lectins. Based on the three dimensional model of KAJ8044242.1, it is possible to suggest that HGA-2 is a lectin that contains the conserved EPN motif. HGA-2 in association with tetracycline, showed an additive effect and synergistic effect against S. aureus ATCC 700698 and E. coli ATCCC 11303, respectively. HGA-2 is a protein with antibacterial potential, when in association with tetracycline the lectin potentiated the effect of the antibiotic. Moreover, the lectin was able to reduce the formation of bacterial biofilms of S. aureus and E.coli. Thus, HGA-2 shows a potential use for the development of new antibacterial drugs.